Spatial and seasonal variation of rainfall contribution by the height spectrum of precipitation systems and associated cloud bulk properties over the South Asia. (21st December 2019) - Roy, Partha; Biswasharma, Rupraj; Deshamukhya, Atri; Sharma, Sanjay
Abstract: The spatial‐seasonal variation of rainfall contribution by the height spectrum of precipitation systems in terms of maximum echo top height of 20 and 40 dBZ (ETH20 dBZ (max) and ETH40 dBZ (max) ) is investigated. The study is carried out during the pre‐monsoon (March–May) and monsoon (June–September) over the continental, coastal and oceanic regions of South‐Asia. For this purpose, 17 years (1998–2014) of TRMM‐PR and 4 years (2007–2010) of CloudSat‐CPR observations are considered. Over the continental (coastal/oceanic) regions, the maximum rainfall contribution is by relatively deeper ETH20 dBZ (max) during the monsoon (pre‐monsoon). During the pre‐monsoon (monsoon), the maximum rainfall contribution by Deep Convective Systems (DCSs) is over the Northern‐Myanmar‐Coast; 55% (Western‐Himalaya‐Indentation; 39%). Over the central Arabian‐Sea and central Bay‐of‐Bengal, rainfall contributions by DCSs are predominantly associated with Tropical Cyclonic Disturbances (TCDs) in the pre‐monsoon season. In terms of ETH40 dBZ (max), the maximum rainfall contribution over the continental region during the pre‐monsoon is by relatively stronger Precipitation Features (PFs) compared to the monsoon. Unlike the other regions, during the pre‐monsoon, over the Western‐Himalaya‐Indentation and Central‐Himalaya‐Foothills, rainfall contribution by Intense Convective Systems (ICSs) is significantly higher compared to DCSs. During the pre‐monsoon (monsoon), the maximum rainfall contribution by ICSs is over the Eastern‐India‐Coast; 35% (Western‐Himalaya‐Indentation; 18%). The rainfall contribution by ICSs during TCDs is insignificant. During both the seasons, the regions of high rainfall contribution by ICSs, DCSs, and shallow PFs are associated with relatively higher (≥400 mg‐m −3 ), moderate (300–350 mg‐m −3 ), and low (<150 mg‐m −3 ) Cloud Ice Water Content (CIWC) in the mixed‐phase region, respectively, suggesting a strong, moderate and weak mixed‐phase processes involved in the respective PFs. TCDs enhance the occurrence of DCSs with moderate CIWC in mixed‐phase region and leading to enhanced rainfall contribution by them over the active cyclone regions. Abstract : Significant spatial‐seasonal variation in rainfall contribution by the height spectrum of precipitation systems is observed over the South‐Asia. During the pre‐monsoon and monsoon seasons, the regions of high rainfall contribution by intense‐convective‐systems, deep convective‐systems, and shallow‐systems are found to be associated with relatively higher (≥400 mg‐m −3 ), moderate (300–350 mg‐m −3 ), and low (<150 mg‐m −3 ) Cloud Ice Water Content in the mixed‐phase region respectively.